Alternative Treatment of a Bleeding Rectal Varix Using an Over-the-Scope Clip. Issue 9 (September 2019) - Sánchez-Luna, Sergio A.; Gulati, Rishabh; Rustagi, Tarun
Abstract : ABSTRACT: Portal hypertension with the subsequent development of portosystemic shunts such as rectal varices is a well-known complication of liver cirrhosis. We discuss the classic options for management of bleeding rectal varices. We present an alternative and not previously described use of an over-the-scope clip to manage bleeding from a rectal varix refractory to management with endoscopic banding.